Outcome of infection following internal fixation of closed fractures - Mohd Yusof, Nazri; Yusof, Abdul Halim (Malaysian Medical Association, 2004)

(untitled)
A retrospective study was done in 30 patients with infected closed fractures treated initially by open reduction and internal fixation. Nineteen fractures involved the femur, 8 the tibia, 2 the radius and 1 the ulna. Twenty-five were diaphyseal and 5 metaphyseal. Twenty-two fractures had initially been treated with plating and 8 with intramedullary nailing. Thirteen patients presented in the acute phase and 17 in the subacute phase of infection. Twenty-two patients presented with low grade infection and 8 with florid infection. The commonest organism isolated was Staphylococcus aureus (80%), of which fifty four percent was resistant to Methicillin (MRSA). This study showed that 77% of infected fractures with a stable implant united even in the presence of infection